MAKNA BONUS BAGI PENGEMUDI TRANSPORTASI ONLINE - Darti Djuharni; Wilujheng Dwi Pangesti (STIE Malangkucecwara, 2020)
The interpretive paradigm used in this study is intended to uncover the meaning of bonuses for online transportation drivers. The existence of benefits felt by the community towards the existence of online transportation, encourages researchers to study it further. Nine online transportation drivers in Malang were used as informants in this study. Interviews were conducted based on the willingness of the drivers and conducted while the person was waiting for the order. Based on the results of the analysis that has been done, the meaning of bonuses revealed in this study are: Fulfillment of Basic Needs, Performance Enhancement, Fulfillment of Safety and Comfort, and Existence of Achievement Assessment